2019
DOI: 10.1017/s003329171900120x
|View full text |Cite
|
Sign up to set email alerts
|

The process and delivery of CBT for depression in adults: a systematic review and network meta-analysis

Abstract: Cognitive-behavioural therapy (CBT) is an effective treatment for depressed adults. CBT interventions are complex, as they include multiple content components and can be delivered in different ways. We compared the effectiveness of different types of therapy, different components and combinations of components and aspects of delivery used in CBT interventions for adult depression. We conducted a systematic review of randomised controlled trials in adults with a primary diagnosis of depression, which included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 40 publications
6
61
0
Order By: Relevance
“…Our typology of interventions and control conditions was based on previous literature, [29][30][31][32]35 piloting, and discussion in our team. Nevertheless, we acknowledge that the process of categorising complex interventions is subjective 40 and future work should agree on a process for node-making as well as agreeing on a taxonomy for classifying psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our typology of interventions and control conditions was based on previous literature, [29][30][31][32]35 piloting, and discussion in our team. Nevertheless, we acknowledge that the process of categorising complex interventions is subjective 40 and future work should agree on a process for node-making as well as agreeing on a taxonomy for classifying psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention and control descriptions are provided in the appendix (p 15). Following classifications adopted in previous reviews,16,[29][30][31][32][33] the content of psychological and psychosocial interventions was classified into five broad intervention types: cognitive behavioural therapy (CBT), behavioural…”
mentioning
confidence: 99%
“…Reviews have shown CBT is effective in reducing depression outcomes for people with clinical depression (López-López et al, 2019 ; NICE, 2009 ). However, when we examined the heterogeneity of effects upon depression outcomes across reviews of CBT for clinical depression, we found the review effects varied greatly and we could not pool across these reviews.…”
Section: Discussionmentioning
confidence: 99%
“…The present ndings contribute to the literature by developing a useful instrument that is necessary to determine the yet to be discovered optimal CBT components and combinations [5], [6], [7]. The results of the EFA showed that SM, BA, CR, AT, and PS could indeed be classi ed as distinct factors representing separate CBT skills.…”
Section: Discussionmentioning
confidence: 59%
“…The rst direction is to derive skills, or combination of skills, that are effective for the entire population of depressed patients. Such optimal combination is yet to be discovered [5] [6] [7]. Towards this solution, several research groups are currently conducting fully factorial randomized controlled trials of CBT optimization [8] [9].…”
Section: Introductionmentioning
confidence: 99%